Analisis Pengaruh Waktu Pembusukan Substrat Roti Basi Terhadap Produksi Energi Listrik Pada Microbial Fuel Cell - Yohana Tisca Tiurma Limbong; M Ramdlan Kirom; Ahmad Qurthobi (eProceedings of Engineering, 2019)
Abstrak Penelitian ini mengenai analisis pengaruh waktu pembusukan substrat roti basi terhadap produksi energi listrik pada microbial fuel cell. Tujuan dari penelitian ini untuk menyelidiki keberadaan roti basi yang mengandung bahan organik, hal ini memiliki potensi besar sebagai sumber energi listrik dengan menggunakan microbial fuel cell. Reaktor yang digunakan adalah MFC dual-chambers dengan setiap kompartemen memiliki dimensi 5 cm x 10 cm x 10 cm. Pada sistem MFC dual-chambers, elektron dihasilkan oleh bakteri dari substrat pada kompartemen anoda dan mengalir menuju elektron katoda, sedangkan proton ditransfer menuju kompartemen katoda melalui jembatan garam. Roti basi digunakan sebagai substrat pada anoda, akuades pada katoda, serta jembatan garam (NaCl 1 M) sebagai media trasnfer proton. Variasi lama waktu inkubasi substrat yaitu selama 1 hari, 3 hari dan 5 hari. Hasil penelitian menunjukkan bahwa pembusukan roti basi paling lama dapat menghasilkan produksi energi listrik yang tertinggi dengan tegangan 0,03669 volt, kuat arus 0,33 miliampere, daya 0,050 mW.m-2 dan energi 12,56989 kilojoule. Kata kunci : Microbial Fuel cell, roti basi, elektroda Abstract Alternative energy sources for fossil-based energy substitutes are needed because fossil energy reserves are decreasing every day. One alternative technology that can be developed is Microbial Fuel Cell (MFC) which utilizes microorganisms to break down the substrate to produce electrical energy. Stale bread is chosen as a source of material to produce electricity because it is economical and can be found easily and abundantly in Indonesia. This research was conducted to investigate the existence of stale bread containing organic matter, this has great potential as a source of electrical energy using microbial fuel cells. The reactor used is a dual-chambers MFC with each compartment having a dimension of 5 cm x 10 cm x 10 cm. In dual-chambers MFC systems, electrons are produced by bacteria from the substrate in the anode compartment and flow into the cathode electrons, while the protons are transferred to the cathode compartment via a salt bridge. Stale bread is used as a substrate at the anode, distilled water on the cathode, and a salt bridge (1 M NaCl) as a proton transfer medium. Variation in substrate incubation time is 1 day , 2 day and 3 day. The results showed that the longest spoilage of bread can produce the highest production of electrical energy with a voltage of 0.03669 volts, current strength of 0.33 milliamperes, power density of 0,050 mW.m-2 and energy of 12,56989 kilojoules. Keywords: Microbial Fuel cell, stale bread, electrode